Microbial evaluation of steam pasteurization and comparison of excision versus sponge sampling recovery - Retzlaff, D.L.; Rueger, S.A.; Phebus, Randall K.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The use of steam pasteurization (SPS400™; Frigoscandia, Bellevue, WA) as a viable commercial-scale intervention method to treat pre-rigor beef carcasses uniformly hasbeen evaluated for temperatures from 180E to 201 ̊F. Effectiveness at lower temperatures(minimum atmospheric temperature of 170 ̊F) has not been evaluated. Previous studies of steam pasteurization used excision sampling. However, the USDA-FSIS has suggested use of nondestructive sampling of chilled beef carcasses for generic Escherichia coli, so we compared excision and sponge sampling in a commercial slaughter facility. Twenty-eight beef carcasses were monitored to determine the effectiveness of steam pasteurization and to compare the two sampling methods. Total aerobic mesophilic bacteria, E. coli, and coliform counts were all reduced (P≤0.01) by steam pasteurization. Sponge sampling of carcasses for E. coli. provided lower recovery (P≤0.01) than excision sampling. None of 28 carcasses tested positive by sponge sampling; however, six of the same microbial carcasses were positive (0.39-23.6 CFU/cm2) by excision sampling immediately adjacent to the sponged area. The SPS 400™ steam pasteurization unit, operating at a minimum atmospheric temperature of 170 ̊F reduced (P≤0.01) all bacterial populations on prerigor beef carcasses. Excision data, compared to previous commercial evaluations of the SPS 400™ at a slightly higher operating atmospheric temperature, provided comparable total reductions, but a few more E. coli survived at 170 F.
Keywords: Beef; Steam pasteurization; Microbial evaluation; Carcasses